CP-036 evaluation of outpatient clinic letters for medication errors. (24th February 2014) - Chindamai, P; Bush, J; Gupta, R; Terry, D
Abstract : Background: It is well recognised that errors are more likely to occur during transitions of care, especially medicines errors. Clinic letters are used as a communication tool during a transition from hospital (outpatient clinics) to primary care (general practitioners). Little is known about medicines errors in clinic letters, as previous studies in this area have focused on medicines errors in inpatient or outpatient prescriptions. Published studies concerning clinic letters largely focus on perceptions of patients or general practitioners in respect to overall quality. Purpose: To investigate medicines errors contained in outpatient clinic letters generated by prescribers within the Neurology Department of a specialist paediatric hospital in the UK. Materials and methods: Single site, retrospective, cross-sectional review of 100 clinic letters generated during March–July 2013 in response to an outpatient consultation. Clinic letters were conveniently selected from the most recent visit of each patient. An evaluation tool with a 10-point scale, where 10 was no error and 0 was significant error, was developed and refined throughout the study to facilitate identification and characterisation of medicines errors. The tool was tested for a relationship between scores and number of medicines errors using a regression analysis. Results: Of 315 items related to neurology mentioned within the letters, 212 items were associated with 602 errors. Common missing information was allergy (97%, n = 97), formulation (60.3%, n = 190), strength/concentration (59%, n = 186) and weight (53%, n = 53). Ninety-nine letters were associated with at least one error. Scores were in range of 4–10 with 42% of letters scored as 7. Statistically significant relationships were observed between scores and number of medicines errors (R 2 = 0.4168, p < 0.05) as well as between number of medicines and number of drug-related errors (R 2 = 0.9719, p < 0.05). Conclusions: Nearly all clinic letters were associated with medicines errors. The 10-point evaluation tool may be a useful device to categorise clinic letter errors. No conflict of interest.